What Caused the Bhopal Gas Tragedy? The Philosophical Importance of Causal and Pragmatic Details. Issue 2 (October 2021) - Hanley, Brian J.
Abstract : In cases in which many causes together bring about an effect, it is common to select some as particularly important. Philosophers since Mill have been pessimistic about analyzing this reasoning because of its variability and the multifarious causal and pragmatic details of how it works. I argue Mill was right to think these details matter but wrong that they preclude philosophical analysis of causal selection. I show that analyzing the pragmatic details of scientific debates about the important causes of the Bhopal Gas Tragedy can illuminate causal reasoning about disasters and shed new light on causality and causal selection.